PEMAHAMAN DAN PENERAPAN AL-ISTIKHDAM DAN AL-ISTIHRAD DALAM SASTRA BAHASA ARAB - Sukma Indriati; Azizah Sabrina Gajah; Devi Humaira Hayati; Harun Al Rasyid (Yayasan Haiah Nusratul Islam, 2025)
The purpose of this study is to analyze the understanding and application of the concepts of Al-Istikhdam and Al-Istihrad in Arabic literature, particularly in the science of Badi', which studies beauty and rhetorical techniques in language. Al-Istikhdam refers to the use of words or expressions chosen with a specific purpose to reinforce a certain message or effect in a literary work, while Al-Istithrad relates to the repetition or addition of unexpected elements to create a dramatic effect or increase the depth of meaning. Both concepts have an important role in creating beauty and expressive power in Arabic. This study examines how these two techniques are applied in classical and modern Arabic literary texts, and their effect on the reader's understanding of the meaning conveyed. In this research, a qualitative approach is used with the method of library research and literature review. This study focuses on scholarly journals. Secondary data is the database used, which is obtained through collecting information from various relevant reading sources, such as books, journals, and online articles. The results of this study are expected to provide a deeper insight into the techniques of Badi' and its contribution to the rich Arabic literary tradition.